A new species of extinct Late Quaternary giant tortoise from Hispaniola - Turvey, Samuel T.; Almonte, Juan; Hansford, James; Scofield, R. Paul; Brocca, Jorge L.; Chapman, Sandra D. (Zootaxa, 2017)
Insular giant tortoise diversity has been depleted by Late Quaternary extinctions, but the taxonomic status of many extinct populations remains poorly understood due to limited available fossil or subfossil material, hindering our ability to reconstruct Quaternary island biotas and environments. Giant tortoises are absent from current-day insular Caribbean ecosystems, but tortoise remains from Quaternary deposits indicate the former widespread occurrence of these animals across the northern Caribbean. We report new Quaternary giant tortoise material from several cave sites in Pedernales Province, southern Dominican Republic, Hispaniola, representing at least seven individuals, which we describe as Chelonoidis marcanoi sp. nov. Although giant tortoise material was first reported from the Quaternary record of Hispaniola almost 35 years ago, tortoises are absent from most Quaternary deposits on the island, which has been studied extensively over the past century. The surprising abundance of giant tortoise remains in both vertical and horizontal caves in Hispaniola’s semi-arid ecoregion may indicate that this species was adapted to open dry habitats and became restricted to a habitat refugium in southeastern Hispaniola following climatic-driven environmental change at the Pleistocene-Holocene boundary. Hispaniola’s dry forest ecosystem may therefore have been shaped by giant tortoises for much of its evolutionary history.